Serine kinases and T lymphocyte biology - Cantrell, Doreen (Henry Stewart Talks, 2011)
T cell development and function, T cell activation, Serine kinase networks, T cell phosphoproteome, Kinases active in CTL, Functions of the CTL phosphoproteins, PKB signal transduction, PKB/Akt role in CTL, Inhibition of PKB, CCR7 and CD62L, Homing ability in CTL, PIP3 & PKB activation, PTEN deletion/down-regulation effect, PKB phosphorylates Foxo1 and Foxo3A, Foxo and CD62L & CCR7 expression, PKB cascade and KLF2, PKB controls T cell trafficking via Foxo